Oral Microbiota-Host Interaction Mediated by Taste Receptors - Dong, Hao; Liu, Jiaxin; Zhu, Jianhui; Zhou, Zhiyan; Tizzano, Marco; Peng, Xian; Zhou, Xuedong; Xu, Xin; Zheng, Xin (Frontiers in Cellular and Infection Microbiology, 2022)
Taste receptors, originally identified in taste buds, function as the periphery receptors for taste stimuli and play an important role in food choice. Cohort studies have revealed that single nucleotide polymorphisms of taste receptors such as T1R1, T1R2, T2R38 are associated with susceptibility to oral diseases like dental caries. Recent studies have demonstrated the wide expression of taste receptors in various tissues, including intestinal epithelia, respiratory tract and gingiva, with an emerging role to participate in the interaction between mucosa surface and microorganisms via monitoring a wide range of metabolites. On the one hand, individuals with different oral microbiome exhibited varied taste sensitivity, suggesting a potential impact of the oral microbiota composition on taste receptor function. On the other hand, animal studies and in vitro studies have uncovered that a variety of oral cells expressing taste receptors such as gingival solitary chemosensory cells, gingival epithelial cells and gingival fibroblasts can detect bacterial signals through bitter taste receptors to trigger host innate immune responses, thus regulating oral microbial homeostasis. This review focuses on how taste receptors, particularly bitter and sweet taste receptors, mediate the oral microbiota-host interaction as well as impact the occurrence and development of oral diseases. Further studies delineating the role of taste receptors in mediating oral microbiota-host interaction will advance our knowledge in oral ecological homeostasis establishment, providing a novel paradigm and treatment target for the better management of dental infectious diseases.